Effects of SNF1 on Maltose Metabolism and Leavening Ability of Baker's Yeast in Lean Dough. Issue 12 (18th November 2015) - Zhang, Cui‐Ying; Bai, Xiao‐Wen; Lin, Xue; Liu, Xiao‐Er; Xiao, Dong‐Guang
Abstract: Maltose metabolism of baker's yeast ( Saccharomyces cerevisiae ) in lean dough is negatively influenced by glucose repression, thereby delaying the dough fermentation. To improve maltose metabolism and leavening ability, it is necessary to alleviate glucose repression. The Snf1 protein kinase is well known to be essential for the response to glucose repression and required for transcription of glucose‐repressed genes including the maltose‐utilization genes ( MAL ). In this study, the SNF1 overexpression and deletion industrial baker's yeast strains were constructed and characterized in terms of maltose utilization, growth and fermentation characteristics, mRNA levels of MAL genes ( MAL62 encoding the maltase and MAL61 encoding the maltose permease) and maltase and maltose permease activities. Our results suggest that overexpression of SNF1 was effective to glucose derepression for enhancing MAL expression levels and enzymes (maltase and maltose permease) activities. These enhancements could result in an 18% increase in maltose metabolism of industrial baker's yeast in LSMLD medium (the low sugar model liquid dough fermentation medium) containing glucose and maltose and a 15% increase in leavening ability in lean dough. These findings provide a valuable insight of breeding industrial baker's yeast for rapid fermentation.